RELATIONSHIP OF ENVIRONMENTAL POLLUTION KNOWLEDGE TO ENVIRONMENTAL RESPONSIBILITY BEHAVIOR - Yulistiana Yulistiana (Green Publisher, 2022)
This study aims to determine the relationship between the Personal Responsibility variable and the Environmental Responsibility Behavior variable at BAPPEDA Kebumen Regency. The selected sample is 52 people with the criteria of civil servants and non civil servants. This research uses survey method. The results of this study concluded that 1) The results of the normality calculation of the estimated YX 2 error obtained L o = 0.04 3 , while L t = 0.0 74 . 2) Homogeneity test obtained c2 count < c2 tables or 48 , 952 < 124 . 3) there is a positive relationship between knowledge of environmental pollution and environmental responsibility behavior with the regression equation = 37.52 + 0.74 X 2 with R = 54 %